Decoding Autism Awareness Posters: Small Stories and Visual Grammar in Malaysian Health Campaigns - Md Yusof, Maslinda; Ahamat, Mohd Iqbal; Lee, Yi Ling; Chong, Seng Tong; Mohd Shkuri, Nur Syafiqah (Al-Azkiyaa - International Journal of Language and Education, 2025)
This study aimed to decode autism health visual contents on social media utilising Kress and van Leeuwen’s compositional metafunction and Bamberg and Georgakopoulou’s small stories framework through narrative stancetaking. The features of four posters collected from the Facebook page of the Malaysian Ministry of Health were assessed qualitatively, focusing on their visuals and narratives. Compositional metafunction was a significant component in the messages delivered through the posters. Information value, salience, and framing were the metafunction subcategories identified. The results also indicated that metafunction contributed to effective autism message delivery to the Malaysian audience. Furthermore, Visual Grammar by Kress and van Leeuwen (2006) was vital in enhancing public understanding of autism. The effort coincides with the aim of the United Nations of achieving inclusivity by 2030 through its sustainable development goals. In this study, an element in the small stories’ framework, narrative stancetaking, was employed, as it can be implemented to analyse social media. Nonetheless, only four posters were selected and analysed in this study, limiting the data collected in this study. Consequently, future studies may consider incorporating more posters from diverse sources. Exploring other metafunctions in understanding the messages delivered through the posters can also be employed.